Evaluation of the Implementation of 5C and 7P Principles with the Mckinsey 7S Framework Model Approach to Credit Distribution at the Commercial Banking Directorate of PT Bank Mandiri (Persero) Tbk - Rahmasari, Gina; Cahyandito, Martha Fani; Tato, Agust (Budapest International Research and Critics University, 2022)
Collection and Distribution of Credit is a very important role of the Bank for the Indonesian economy, considering that the flow of funds is used for various economic needs, both consumption, business capital, and investment channeled through the Bank. Loans disbursed are the result of a decision from a process carried out by applying the precautionary principle, which is expected to minimize the risk of non-performing loans, as seen from the NPL ratio. Generally, every Bank is required to apply the prudential principle, through the 5C principles and the 7P principles. This study uses descriptive methods to identify problems, explain symptoms, and examine conditions and prevailing practices based on the information collected. The results showed that the respondents' responses regarding the application of the 5C principle scored very high, the implementation of the 7P principles obtained a high score, the respondents' responses to credit distribution obtained a high score. Based on the results of simultaneous hypothesis testing, it can be stated that Principle 5C and Principle 7P simultaneously affect credit distribution at the Commercial Banking Directorate of PT Bank Mandiri (Persero) Tbk.